1999
DOI: 10.1364/ao.38.006845
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide laser fabrication of fused-fiber couplers and tapers

Abstract: We report the development of a fiber taper and fused-fiber coupler fabrication rig that uses a scanning, focused, CO(2) laser beam as the heat source. As a result of the pointlike heat source and the versatility associated with scanning, tapers of any transition shape and uniform taper waist can be produced. Tapers with both a linear shape and an exponential transition shape were measured. The taper waist uniformity was measured and shown to be better than +/-1.2%. The rig was also used to make fused-fiber cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 7 publications
0
63
0
2
Order By: Relevance
“…Low loss fibers down to 50 nm have been made using the self-modulation flame method. 22,38 Alternative heat sources include a focused CO 2 laser, which is scanned along the fiber [39][40][41][42][43] or a stationary CO 2 laser focused onto the fiber via a diffractive optical element. 44 Microfurnaces in the form of electric strip heaters, [45][46][47][48][49] and sapphire tubes 50,51 have also been used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low loss fibers down to 50 nm have been made using the self-modulation flame method. 22,38 Alternative heat sources include a focused CO 2 laser, which is scanned along the fiber [39][40][41][42][43] or a stationary CO 2 laser focused onto the fiber via a diffractive optical element. 44 Microfurnaces in the form of electric strip heaters, [45][46][47][48][49] and sapphire tubes 50,51 have also been used.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the minimum achievable taper diameter when using a CO2 laser is larger than that for a flame. [39][40][41][42][43][44] On the other hand, electric strip heaters and microfurnaces can produce submicron-sized fibers, but difficulty in engineering the heater's hotzone for the fabrication of microstructured fibers is a critical disadvantage. Though the basic flame pulling rig system is one of the most well-known methods for achieving arbitrary biconical MNF shapes, it is considered a challenging task because of the technical difficulties in maintaining uniformity and adiabaticity of the taper due to flame instabilities caused by gas regulation and environmental factors, such as air flow, during the tapering process.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore reasonable to assume that the insertion losses of the device were dominated by the taper losses, which are believed to result from the sharp transition between the fiber-guided mode and the cladding-guided mode in the taper region. It is possible to reduce taper loss to as low as 0.1 dB by using an improved fiber taper fabrication technique as described in [9].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…For a 2 m diameter taper at a wavelength of 1550 nm, the fraction of power in the core is nearly 96%. 7 Recent discussions on the form of the evanescent field have shown the spatial extent of the radial component of the field to greatly increase for diameters less than 3 m. 7,8 It has also been reported that efficient coupling of light into submillimeter sized silica microspheres is possible for taper diameters up to 4.5 m. 9 The four most widely exploited means of achieving micron-sized tapers are by flame, 5,10,11 CO 2 laser heating, 12 microfurnace, 13,14 and, to a lesser extent, fusion splicer. 4 While subwavelength diameters have been shown to be achievable with the flame method, it presents significant technical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…16 Previous reported attempts of producing tapers using the CO 2 laser technique have achieved a diameter of 4.6 m with a CO 2 laser power of 13 W and full width at half maximum ͑FWHM͒ spot size of 820 m using a galvanometer mirror scanner. 12 In this article we describe a reliable method of fabricating low loss 3-4 m diameter tapers as well as the possibility of fabricating bottle resonators using a 25 W CO 2 laser. In recent years, interest in the use of microspherical resonators in cavity QED experiments has increased.…”
Section: Introductionmentioning
confidence: 99%